BIMBINGAN BELAJAR SISWA SEKOLAH DASAR (SD) DI PERPUSTAKAAN DAERAH KABUPATEN LANDAK - Tuminah; Nasri Tupulu; Mauri Arpin Arus; Ibrah Fastabiqi Bawana Mukti; Is Sandra Rio; Fransiska Berti (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Tutoring is increasingly common in big cities; almost all parents register their children to take part in existing tutoring. This is done to catch up on lessons that are considered difficult. For parents who have sufficient income, paying for guidance is not a problem. However, for parents who have limited income, paying for tutoring is a very burdensome thing. Seeing the phenomenon that occurred in the villages of Ngabang subdistrict, Landak district, we, a team of service members from the Santo Agustinus Hippo Catholic University, collaborated with the Regional Library of Landak district to provide a Tutoring Service for elementary school students from grades one to five. The tutoring is carried out in the Regional Library building, and the teaching staff are Mathematics Education and English Education students. This guidance is free of charge for elementary school (SD) children who live around the Ngabang sub-district. The aim of this service is to help elementary school children who have difficulty learning mathematics and English. Meanwhile, his parents were unable to pay for tutoring fees. Through this tutoring, elementary school students who experience learning difficulties can overcome them. Keywords: Tutoring, free of charge, Elementary School Students, Mathematics, English.